Urolithin A Protects Chondrocytes From Mechanical Overloading-Induced Injuries - He, Yuchen; Yocum, Lauren; Alexander, Peter G; Jurczak, Michael J; Lin, Hang (Frontiers in Pharmacology, 2021)
Physiological mechanical stimulation has been shown to promote chondrogenesis, but excessive mechanical loading results in cartilage degradation. Currently, the underlying mechanotransduction pathways in the context of physiological and injurious loading are not fully understood. In this study, we aim to identify the critical factors that dictate chondrocyte response to mechanical overloading, as well as to develop therapeutics that protect chondrocytes from mechanical injuries. Specifically, human chondrocytes were loaded in hyaluronic hydrogel and then subjected to dynamic compressive loading under 5% (DL-5% group) or 25% strain (DL-25% group). Compared to static culture and DL-5%, DL-25% reduced cartilage matrix formation from chondrocytes, which was accompanied by the increased senescence level, as revealed by higher expression of p21, p53, and senescence-associated beta-galactosidase (SA--Gal). Interestingly, mitophagy was suppressed by DL-25%, suggesting a possible role for the restoration mitophagy in reducing cartilage degeneration with mechanical overloading. Next, we then treated the mechanically overloaded samples (DL-25%) with Urolithin A (UA), a natural metabolite previously shown to enhance mitophagy in other cell types. qRT-PCR, histology, and immunostaining results confirmed that UA treatment significantly increased the quantity and quality of cartilage matrix deposition. Interestingly, UA also suppressed the senescence level induced by mechanical overloading, demonstrating its senomorphic potential. Mechanistic analysis confirmed that UA functioned partially by enhancing mitophagy. In summary, our results show that mechanical overloading results in cartilage degradation partially through the impairment of mitophagy. This study also identifies UA’s novel use as a compound that can protect chondrocytes from mechanical injuries, supporting high-quality cartilage formation/maintenance.